Extracellular microRNAs exhibit sequence-dependent stability and cellular release kinetics - Coenen-Stass, Anna M. L. (RNA Biol, 2019)
Multiple studies have described extracellular microRNAs (ex-miRNAs) as being remarkably stable despite the hostile extracellular environment, when stored at 4ºC or lower. Here we show that many ex-miRNAs are rapidly degraded when incubated at 37ºC in the presence of serum (thereby simulating physiologically relevant conditions). Stability varied widely between miRNAs, with half-lives ranging from ~1.5 hours to more than 13 hours. Notably, ex-miRNA half-lives calculated in two different biofluids (murine serum and C2C12 mouse myotube conditioned medium) were highly similar, suggesting that intrinsic sequence properties are a determining factor in miRNA stability. By contrast, ex-miRNAs associated with extracellular vesicles (isolated by size exclusion chromatography) were highly stable. The release of ex-miRNAs from C2C12 myotubes was measured over time, and mathematical modelling revealed miRNA-specific release kinetics. While some ex-miRNAs reached the steady state in cell culture medium within 24 hours, the extracellular level of miR-16 did not reach equilibrium, even after 3 days in culture. These findings are indicative of miRNA-specific release and degradation kinetics with implications for the utility of ex-miRNAs as biomarkers, and for the potential of ex-miRNAs to transfer gene regulatory information between cells.